2019
DOI: 10.1055/a-0990-8898
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-RM2 PET in PSMA- positive and -negative prostate cancer patients

Abstract: Aim 68Ga-PSMA-11 is the gold standard for molecular imaging of prostate cancer. However, recurrent tumor manifestations or metastases cannot be detected in every case. Therefore, we investigated if there is an additive value of the gastrin-releasing peptide receptor (GRP-R) ligand 68Ga-RM2 compared to the well-established 68Ga-PSMA-11 in patients with (Group 1) and without (Group 2) pathologic PSMA-expression in different tumor stages. Patients and Methods Sixteen men (median age: 74 years, range 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Participants with suspected BCR PC after primary treatment were prospectively enrolled in 3 clinical trials evaluating the performance of 68 Ga-RM2 (NCT 02624518), 68 Ga-PSMA11 (NCT02673151) and 18 F-DCFPyL (NCT03501940). Twenty-three patients had both 68 Ga-RM2 PET/MRI and 68 Ga-PSMA11 PET/CT, while another 27 patients had both 68 Ga-RM2 PET/MRI and 18 F-DCFPyL PET/CT.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants with suspected BCR PC after primary treatment were prospectively enrolled in 3 clinical trials evaluating the performance of 68 Ga-RM2 (NCT 02624518), 68 Ga-PSMA11 (NCT02673151) and 18 F-DCFPyL (NCT03501940). Twenty-three patients had both 68 Ga-RM2 PET/MRI and 68 Ga-PSMA11 PET/CT, while another 27 patients had both 68 Ga-RM2 PET/MRI and 18 F-DCFPyL PET/CT.…”
Section: Patient Populationmentioning
confidence: 99%
“…Commonly used radiopharmaceuticals targeting PSMA include 68 Ga-PSMA-HBED-CC ( 68 Ga-PSMA11) (6) and 18 F-DCFPyL (7). Another class of radiopharmaceuticals used for the assessment of PC patients are the gastrin releasing peptide (GRP) analogs.…”
Section: Introductionmentioning
confidence: 99%
“…However, high interindividual variability of agreement between the uptake of this radioligand and histopathology has been observed [ 164 ]. In a study comparing 68 Ga-PSMA-11 with 68 Ga-RM2, no PSMA-negative patients showed RM2-accumulation [ 165 ]. Both 68 Ga-PSMA-11 and 68 Ga-RM2 identified the same cases of local recurrence, but 68 Ga-RM2 scans were negative in some of the patients with PSMA-positive bone or lymph node metastases.…”
Section: Other Radioligands and Targets In Prostate Cancer In Comparison With Psma Based Targetingmentioning
confidence: 99%
“…Both 68 Ga-PSMA-11 and 68 Ga-RM2 identified the same cases of local recurrence, but 68 Ga-RM2 scans were negative in some of the patients with PSMA-positive bone or lymph node metastases. 68 Ga-RM2 scans did reveal some additional metastatic bone lesions but did not affect the line of treatment [ 165 ]. Theranostic 177 Lu-RM2 therapy was well tolerated in mCRPC patients with the pancreas being the critical organ [ 166 ].…”
Section: Other Radioligands and Targets In Prostate Cancer In Comparison With Psma Based Targetingmentioning
confidence: 99%
“…There is, therefore, a high detecting potential as a second primary cancer in the clinical follow-up of other malignancies. Malignancy is present in a significant portion of PIs occasionally encountered in routine 18F-FDG PET/CT scans [2,3,12,14,16]. According to a meta-analysis investigating six studies comprising 47,925 patients, the pooled prevalence of incidental prostatic uptake detected using 18F-FDG PET/CT was 1.8 % (95 % CI: 1.3-2.3) and the malignancy ratio of PI was 17 % (95 % CI: 1.3-2.3) [5].…”
Section: Discussionmentioning
confidence: 99%